Wireless Communication Networks for Gas Turbine Engine Testing. (14th March 2012) - Dai, Xuewu; Sasloglou, Konstantinos; Atkinson, Robert; Strong, John; Panella, Isabella; Yun Cai, Lim; Mingding, Han; Chee Wei, Ang; Glover, Ian; Mitchell, John E.; Schiffers, Werner; Dutta, Partha S.
Abstract : A new trend in the field of Aeronautical Engine Health Monitoring is the implementation of wireless sensor networks (WSNs) for data acquisition and condition monitoring to partially replace heavy and complex wiring harnesses, which limit the versatility of the monitoring process as well as creating practical deployment issues. Augmenting wired with wireless technologies will fuel opportunities for reduced cabling, faster sensor and network deployment, increased data acquisition flexibility, and reduced cable maintenance costs. However, embedding wireless technology into an aero engine (even in the ground testing application considered here) presents some very significant challenges, for example, a harsh environment with a complex RF transmission channel, high sensor density, and high data rate. In this paper we discuss the results of the Wireless Data Acquisition in Gas Turbine Engine Testing (WIDAGATE) project, which aimed to design and simulate such a network to estimate network performance and derisk the wireless techniques before the deployment.